On‐target sorafenib toxicity predicts improved survival in hepatocellular carcinoma: a multi‐centre, prospective study. Issue 8 (2nd March 2017) - Howell, J.; Pinato, D. J.; Ramaswami, R.; Bettinger, D.; Arizumi, T.; Ferrari, C.; Yen, C.; Gibbin, A.; Burlone, M. E.; Guaschino, G.; Sellers, L.; Black, J.; et al.
Summary: Background: Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide and has high mortality despite treatment. While sorafenib has a survival benefit for patients with advanced HCC, clinical response is highly variable. Aim: To determine whether development of sorafenib toxicity is a prognostic marker of survival in HCC. Methods: In this prospective multicentre cohort study, patients with advanced‐stage HCC receiving sorafenib were recruited from five international specialist centres. Demographic and clinical data including development and grade of sorafenib toxicity during treatment, radiological response to sorafenib and survival time (months) were recorded prospectively. Results: A total of 634 patients with advanced‐stage HCC receiving sorafenib were recruited to the study, with a median follow‐up of 6692.3 person‐months at risk. The majority of patients were male (81%) with Child–Pugh A stage liver disease (74%) and Barcelona Clinic Liver Cancer stage C HCC (64%). Median survival time was 8.1 months (IQR 3.8–18.6 months). 94% experienced at least one sorafenib‐related toxicity: 34% diarrhoea, 16% hypertension and 37% hand‐foot syndrome (HFS). Twenty‐one per cent ceased sorafenib due to toxicity and 59% ceased treatment due to progressive disease or death. On multivariate analysis, sorafenib‐related diarrhoea (HR 0.76, 95% CI 0.61–0.95, P = 0.017), hypertension (HR 0.531, 95% CI 0.37–0.76, P < 0.0001) and HFS (HR 0.65, 95% CI 0.51–0.81, P < 0.0001) were all significant independent predictors of overall survival after adjusting for age, severity of liver disease, tumour stage and sorafenib dose. Conclusion: Development of sorafenib‐related toxicity including diarrhoea, hypertension and hand‐foot syndrome is associated with prolonged overall survival in patients with advanced‐stage HCC on sorafenib.